A novel three phase cascaded multilevel inverter topology - Hasan, M.; Abu-Siada, Ahmed (2017)
A new Cascaded Multilevel inverter (CMLI) concept is presented in this paper, which is applicable to any existing CMLI topologies. The proposed new three phase MLI topology consists of level generator stage (LGS) and phase generator stage (PGS). While the PGS contains a specific structure of 12-semiconductor switches and 12-diodes, the LGS structure depends on the existing CMLI topologies. The main feature of the proposed new CMLI topology is to reduce the device counts of the existing CMLI topologies while they are implemented as dc/ac three phase power converters. The conventional cross-switched CMLI topology is considered as LGS in the experimental prototype. Simulation and experimental results are provided to verify the proposed new three phase CMLI concept.